Beta Estimation Practice and its Reliability Biasness Towards Aggressive Stocks: An Empirical Evidence from NSE - Sanghi, Neeraj; Bansal, Gaurav (Indian Journal of Finance, 2011)
In finance literature, ’beta’ possesses a prominent place as a measurement statistic of systematic risk arising out of economic wide uncertainties. As a matter of fact, Index Model is very common in practice as leading stock exchanges of India make use of this model for beta estimation. Our study aims at this approach of beta estimation for establishing how beta coefficients for aggressive stocks prove to be more reliable than defensive stocks. Since Index Model is linear and envisages the premise of Simple Linear Regression, the researchers compare reliability of beta coefficients for aggressive and defensive stocks on the basis of R-squired statistic.